Pocket Size Ultra-Sound versus Cardiac Auscultation in Diagnosing Cardiac Valve Pathologies: A Prospective Cohort - Zeller, Lior; Fuchs, Lior; Maman, Tomer; Shafat, Tali; Faingelernt, Yaniv; Barski, Leonid; Liel-Cohen, Noah; L. Kobal, Sergio (International Journal of Medical Students, 2022)
Background: Pocket-size ultrasound devices are used to perform focused ultrasound studies (POCUS). We compared valve malfunction diagnosis rate by cardiac auscultation to POCUS (insonation), both conducted by medical students. Methods: A prospective cohort study was conducted among subjects with and without clinically relevant valve dysfunction. Inclusion criteria for subjects with a clinically relevant valve dysfunction was based on the presence of at least one moderate severity valve pathology identified by echocardiography. Three final-year medical students examined the patients. Each subject underwent auscultation and a POCUS using a pocket-size ultrasound machine. Sensitivity and specificity were calculated. Results: The study included 56 patients. In 18 patients (32%) no valve pathology was found. Nineteen patients (34%) had at least two valvular pathologies. Sixty valve lesions were present in the entire cohort. Students' sensitivity for detecting any valve lesion was 32% and 64% for auscultation and insonation, respectively, and specificity was similar. The sensitivity for diagnosing mitral regurgitation, mitral stenosis, and aortic regurgitation rose significantly by using POCUS compared to auscultation alone. When using POCUS, students identified valvular pathologies in 22 cases (39%) from the patients with at least two valve dysfunctions, and none when using auscultation. Conclusions: Final-year medical students' competency to detect valve dysfunction by performing cardiac auscultation is poor. Cardiac ultrasound-focused training significantly improved medical students' sensitivity for diagnosing a variety of valve pathologies.